The Relationship Between Management Skills and Teaching Effectiveness of Primary School Teachers in the Eastern Banai District of Davao - Zouheiry, Ziad (Journal of Research in Vocational Education, 2024)
This study aimed to determine the relationship between public elementary school teachers' managerial skills and instructional efficacy in Banaybanay District, Davao Oriental. This study utilized the descriptive-correlational design with one hundred fifty elementary school teachers selected using a stratified random sampling technique. In gathering data, the researcher adapted a survey questionnaire for managerial skills and instructional efficacy. Ethical considerations were observed in data collection. The collated data were subjected to statistical tests such as mean, Pearson's r, and multiple linear regression. Findings showed that the extent of managerial skills is extensive, which means their managerial skills are often observed. The extent of instructional efficacy is very extensive, which means that their instructional efficacy is always observed. There was a moderately significant relationship between managerial skills and instructional efficacy. Technical skills were the domain of managerial skills that influenced instructional efficacy. The Department of Education should consider incorporating managerial skill development into more extensive educational programs and activities. Recognizing the role of managerial skills in teachers' instructional efficacy allows policymakers and planners to commit resources and support programs that improve these skills among teachers.